Reunion: leadership and the longing to belong - Colonna, Jerry (New York Harper Business, 2023)
Executive coach Jerry Colonna encourages leaders to consider the ways they have been complicit in, and benefited from, the conditions in the world they say they'd like to change and shows them the path to creating new systems of inclusion for everyone.
Keywords: Management